Foreign direct investment, remittances, real exchange rate, imports, and economic growth in Ghana: An ARDL approach - John Kwaku Mensah Mawutor; Ernest Sogah; Freeman Gborse Christian; Desmond Aboagye; Alexander Diani Kofi Preko; Barbara Deladem Mensah; Olivia Nanakua Boateng (Cogent Economics & Finance, 2023)
The main objective of this quantitative study is to ascertain the effect of foreign direct investment, real exchange rate, remittances, and import on economic growth in Ghana. Secondary data on gross domestic product, foreign direct investment, real exchange rate, remittances, import, and gross capital formation from 1980 to 2018 were analyzed. The study employed Autoregressive Distributed Lag for the econometrics analysis. The study found that foreign direct investment, real exchange rate, remittances, import, and gross capital formation cointegrates with economic growth. The main findings are that foreign direct investment, real exchange rate, import, and remittances matter from growth perspective. Remittances have a positive and significant effect on economic growth in Ghana both for the short run and the long run. The study also revealed that foreign direct investment, real exchange rate, and imports have a negative and significant effect on the growth process of Ghana's economy for both the short run and the long run. The study recommends that the Ministry of Finance, Ghana, financial analysts and other policy makers should undertake steps to reduce imports and attract more remittances inflows to attain long-run economic growth. In addition, the economy must concentrate on viable exchange rate policies such as undervaluation of currency to stimulate sustainable economic growth.
Keywords: F43; 330; foreign direct investment; foreign remittances; GDP; imports; real exchange rate Ghana